The impact of first eye cataract surgery on mental health contacts for depression and/or anxiety: a population‐based study using linked data. (16th April 2013) - Meuleners, Lynn B.; Hendrie, Delia; Fraser, Michelle L.; Ng, Jonathon Q.; Morlet, Nigel
Abstract: Purpose:  Cataract is the leading cause of reversible blindness worldwide, and the incidence of cataract surgery is projected to increase as the population ages. Gaining an understanding of the effects of cataract surgery on a range of health outcomes is important for maintaining the health and safety of older adults. Methods:  A before and after cohort study was conducted using the Western Australian Hospital Morbidity Data System, Mental Health Information System and the Western Australian Death Registry. Results:  Of the 21 110 patients who underwent cataract surgery in one eye only, 295 had mental health contacts for depression and/or anxiety 1 year before ( n  = 158) or 1 year after ( n  = 137) surgery. Results from Poisson generalized estimating equations showed a significant decrease of 18.80% (p ≤ 0.001) in the number of mental health contacts for depression and/or anxiety the year after cataract surgery after accounting for potential confounding factors. A 27.46% increase in mental health contacts the year after cataract surgery was reported by women compared with men (95% CI: 1.08–1.50). Those living in remote areas had less contact with mental health services compared with those living in metropolitan areas (adjusted risk ratio 0.62, 95% CI: 0.46–0.84). The corresponding reduction in health care costs for treatment of depression and/or anxiety was 28%. Conclusion:  Further research should be conducted to collect information on the utilization of health care resources not captured in this study, namely community‐based services, visits to general practitioners and/or emergency departments as well as medication usage such as antidepressants.